Pembelajaran IPA Materi Tumbuhan sebagai Sumber Kehidupan Bumi melalui Strategi Joyfull Learning pada Kelas IV di SDN Poris Pelawad 5 - Bella Shadila Sarmadi; Rizki Zuliani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effectiveness of teaching science material on plants as a source of life on earth through the joyful learning strategy in grade IV at SDN Poris Pelawad 5. Education plays an important role in shaping the cognitive, psychomotor, and affective abilities of students. This study employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that teaching science about plants as a source of life using the joyful learning strategy can have a positive impact on students. The joyful learning strategy can be implemented as an effort to create an enjoyable and meaningful learning process in elementary schools.